A journey towards a community - Lituañas, Cyril Ryan A. (Animo Repository, 2008)
Chaplains and animators take a big role in animating the Student Catholic Action of the Philippines. The National Secretariat and the Formation team offer a lot of developmental formation programs to the students and members of the movement. In order to implement the programs to the grassroots level, the Diocesan Formation Team organizes trainings to effectively run the programs to the diocesan and unit levels. The main contacts of the movement in program implementation are animators and chaplains. Sometimes, due to the busy schedules our animators and chaplains have, the programs are implemented by the National Secretariat without the animators' full knowledge of the program. Thus, the animators in the different units of the diocese cannot implement well due to lack of knowledge in handling the program. Community building is necessary to help the movement become efficient and effective in running the programs. The Student Catholic Action of the Philippines is defined as an organized group of students, striving to become a community of Disciples of Jesus Christ by being evangelized and evangelizing. The movement does not only limiting the students to become an organized group and does a lot of activities for others. The movement is all about building a community of Disciples of Jesus Christ who are evangelizing other communities. One of the core values of the movement is community building that is rooted in the love of Jesus Christ. The session hopefully answers the needs of the animators and chaplains to build as a community. The module can be run for 2 hours.